A systematic review of risks and benefits of sitagliptin and saxagliptin monotherapies and metformin combination therapies - G, Vishvas (Indian Journal of Pharmacy Practice)
India has the highest prevalence of diabetes (50.8 million people). Sitagliptin and saxagliptin are the two newer drugs approved for the treatment of type 2 diabetes mellitus. The purpose of this paper is to conduct a systematic literature review of the pharmacological and pharmacoeconomical profiles of sitagliptin and saxaglitpin. Using the MeSH terms in PubMed, a total of four searches were conducted: only sitagliptin, only saxagliptin, and sitagliptin and saxagliptin combined with economics, separately.Various articles were found and analyzed: only sitagliptin (n=125), only saxagliptin (n=34), sitagliptin+economics (n=11), and saxagliptin+economics (n=3). These searches were then narrowed down using the inclusion and exclusion criteria: only sitagliptin (n=26), only saxagliptin (n=9), sitagliptin+economics (n=0), and saxagliptin+economics (n=0). The pooled results of clinical trials show that sitagliptin and saxaglitpin have a good general safety profile. However, no formal economic evaluation of sitagliptin and saxaglitpin in India were found during the search. Formal economic evaluations of sitagliptin and saxaglitpin costs and consequences are required.